2019
DOI: 10.1111/jcmm.14244
|View full text |Cite
|
Sign up to set email alerts
|

Increased level of fibrinogen chains in the proteome of blood platelets in secondary progressive multiple sclerosis patients

Abstract: Epidemiological studies indicate a high risk of stroke, heart failure and myocardial infarction in patients with multiple sclerosis, especially in its secondary progressive (SPMS) phase. Some ischaemic events are directly associated with abnormal platelet functions and their prothrombotic activity. Recent reports, including this study, confirm the increased activation of circulating platelets in SPMS, and also show increased platelet reactivity, among other responses, as well as strong aggregation. In this cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…In our previous work, analyzing proteome of platelets using a 2-dimensional electrophoresis (2-DE) method together with mass spectrometry (MALDI/TOF-TOF) analysis, we reported a higher level of α2M in SP MS patients compared to control group [ 18 ]. It is mainly produced by the liver, but also locally synthesized by blood cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, analyzing proteome of platelets using a 2-dimensional electrophoresis (2-DE) method together with mass spectrometry (MALDI/TOF-TOF) analysis, we reported a higher level of α2M in SP MS patients compared to control group [ 18 ]. It is mainly produced by the liver, but also locally synthesized by blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…The chronic activation of blood platelets in SP MS, as expressed by high levels of activation markers, altered mitochondrial function, and increased platelet reactivity, has been proven in our previous studies to focus exclusively on the progressive stage of MS, characterized with an especially high risk of CVD [ 15 , 16 , 17 ]. Furthermore, our findings have demonstrated changes in the protein profile, manifesting an enhanced level of blood coagulation factors [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fibrin clot formation, leading to vessel occlusion, represents the terminal step in the atherothrombotic process and involves a variety of interactions between coagulation factors and blood platelets [ 132 ]. Many studies, including our research, indicate an increased number of platelet-derived microparticles and enhanced P-selection expression, which are accepted markers of platelet activation in EAE/MS [ 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ]. Disruption of the BBB permeability causes a massive infiltration of many leukocytes that elicit neurotrophic changes, leading to demyelination in the CNS [ 142 ].…”
Section: The Effect Of Metformin On Haemostasis and The Functioninmentioning
confidence: 71%
“…However, available clinical data have confirmed the elevated activation of circulating platelets in MS [48]. Our previous study revealed an increase in the prothrombotic and proinflammatory properties of platelets [11,49,50]. In neurobiological studies, blood platelets are regarded as a cellular model for the analysis of metabolic pathways related to the pathogenesis of MS and the regulation of oxidative stress [49,51].…”
Section: Discussionmentioning
confidence: 95%